Outcomes of male circumcision performed by medical doctors and non–doctor health workers in central Uganda - Kibansha Matumaini, Hope; Batte, Anthony; Otwombe, Kennedy; Lebotsa, Emily; Luboga, Sam (Research Square, 2020)
Task shifting for male circumcision is still a challenge. The aim of this study was to evaluate the outcomes of circumcision conducted by doctors compared to non-doctors in Kampala, Uganda Results: In this prospective cohort study, we observed and followed 274 males at 3 health facilities in Kampala, Uganda. Each participant was observed during the circumcision procedure, monitored for 2 hours post-surgery and assessed at 24hours, 3 days and after one week for adverse events. The mean age of the circumcised men was 24.82 (6.36) years. Of the circumcisions, 19.3% (53/274) were carried out by doctors while 80.7% (221/274) by non-doctor health workers. About 5.47% (15/274) experienced adverse events and the proportions by cadre were similar; medical doctors (5.66% [3/53]) and non-doctor health workers (5.43% [12/221]), p=0.99. Seven patients had evidence of pus discharge (all had been operated by non-doctors), only 2 patients had bleeding at 2 hours (one by medical doctor and one by nondoctor), 4 patients had evidence of excessive skin removal (2 by medical doctor vs 2 by non-doctors). There was no reported urethral injury or glans amputation. These results indicate that non-doctor health workers can offer circumcision services safely with low adverse event rates.
Keywords: Circumcision; Uganda; Non-medical doctors